2001
DOI: 10.1038/sj.bmt.1702858
|View full text |Cite
|
Sign up to set email alerts
|

Extensive clonal expansion of T lymphocytes causes contracted diversity of complementarity-determining region 3 and skewed T cell receptor repertoires after allogeneic hematopoietic cell transplantation

Abstract: Summary:We previously described skewed repertoires of the T cell receptor-␤ chain variable region (TCRBV) and the TCR-␣ chain variable region (TCRAV) soon after allogeneic hematopoietic cell transplantation. To determine the characteristics of skewed TCRBV after transplantation, we examined the clonality of T lymphocytes carrying skewed TCRBV subfamilies and determined the CDR3 sequences of expanded T cell clones. In all 11 recipients examined, TCR repertoires were skewed, with an increase of certain TCRBV sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…5 This results from the extensive clonal expansion of a limited number of T cells in the graft. 6 Skewed TCR repertoires accompany accumulation of the CD28 Ϫ fraction in both CD4 + and CD8 + T cells. 7,8 Since accumulating evidence indicates an association between the loss of CD28 expression and T lymphocyte aging, 9,10 posttransplant skewing of the TCR repertoires probably results from chronic antigen stimulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This results from the extensive clonal expansion of a limited number of T cells in the graft. 6 Skewed TCR repertoires accompany accumulation of the CD28 Ϫ fraction in both CD4 + and CD8 + T cells. 7,8 Since accumulating evidence indicates an association between the loss of CD28 expression and T lymphocyte aging, 9,10 posttransplant skewing of the TCR repertoires probably results from chronic antigen stimulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 To address whether or not the clonally expanded T cells in circulating blood recognize the same antigen as those expanded in GVHD lesions, we compared the usage of TCRAV and TCRBV subfamilies and the CDR3 sequences of clonally expanded T cells from blood and tissues. Since expanded T cells in the blood were not necessarily clonal/oligoclonal, 6 clonality was first determined by TCRBV-CDR3 size spectratyping (Figure 4), then the CDR3 sequences of clonally expanded T cells were analyzed. Table 6 shows that usage of the TCRBV subfamily by T cells clonally expanded in the blood and the structure of CDR3 of those lymphocytes differed from those of T lymphocytes expanded in GVHD tissues.…”
Section: Different Usage Of Tcrbv Subfamily and Cdr3 Sequence In T Lymentioning
confidence: 99%
“…However, direct evidence of the antigens that are responsible for maintaining the clonal expansion of donorderived mature TCRab+ T lymphocytes for many years after transplant remains elusive. We reported that recipients of allogeneic bone marrow grafts have clonally expanded TCRab+ T lymphocytes soon after transplantation, leading to a skew of TCR repertoires, 3,6 and that the usage of TCRAV and TCRBV by the clonally expanded T lymphocytes and their CDR3 sequences differ between the GVHD and blood. 40 Thus, the clonal expansion of T cells in blood does not necessarily mean allogeneic T-cell responses.…”
Section: Peripheral Expansion Of T Cells After Allo-bmtmentioning
confidence: 99%
“…4 Moreover, we found that a skew of the T-cell repertoire can be caused by the clonal expansion of TCRab+CD8+CD28À T cells, 5 and that consensus motifs of amino acids are observed in the complementarity-determining region 3 (CDR3) of clonally expanded T cells among distinct recipients. 6 Animal studies have shown that injecting athymic mice with a limited number of mature T lymphocytes skews the T-cell repertoire, the regeneration of which is affected by the host antigenic milieu. 7 Therefore, the above features of T-cell repertoire reconstitution suggest that the peripheral expansion of donor-derived mature T lymphocytes plays a certain role in T-cell regeneration after human HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…When immunodeficient animals, such as athymic (lacking thymus) mutants and in several types of knock-out animals are transplanted with a sub-optimal variety of syngenic T lymphocytes, these lymphocytes overexpand and may create fatal pathogenic situations 52,53 . A very high synthesis of IgE is included as an unexplained component of these expansions 54 .…”
Section: Lymphopoiesis Stimulated By Lymphopenia (Or "Homeostatic") Amentioning
confidence: 99%